Effect of Lecture on Risk Perception on Occupational Hazards of Barangay Health Workers in the Municipality Of Mahayag, Zamboanga Del Sur - Said, Mishaal C. (Philippine Journal of Labor and Industrial Relations, 2024)
Barangay health workers are crucial to execution of the programs of the Department of Health (DOH). Workplace hazards may harm their health. Risk perception on occupational health hazards affects preventive behavior. The study compares the risk perception of the barangay health workers in the municipality of Mahayag, Zamboanga del Sur, on occupational hazards before and after the intervention. The study employs a pre- and postinterventional design. Total count sampling got 72 respondents enrolled in the study. Pre- and post-lecture questionnaires were used. Results revealed that the lecture improved the risk perception on biological, physical, and ergonomic hazards. There was no improvement in risk perception noted on  psychosocial hazards and mechanical hazards. The study concludes that lecture using the Barangay Health Workers Reference Manual improved risk perception of some occupational hazards. The study recommends full adoption of the manual’s chapter on occupational safety, health and regular occupational safety, and health trainings for barangay health workers.